Beyond bilingualism : multilingualism and multilingual education - Cenoz, Jasone; Genesee, Fred (Multilingual matters (Series), 1998)
This book presents theoretical, empirical and practical bases for implementing multilingual education programs to prepare students for a multilingual world. The authors address issues such as teacher education and multilingual acquisition.